Why Do They Enroll in This Course? Undergraduates’ Course Choice From a Motivational Perspective - Lee, Hye Rin; von Keyserlingk, Luise; Arum, Richard; Eccles, Jacquelynne Sue (Frontiers in Education, 2021)
Why do students pick various courses? Interdisciplinary research has highlighted the role of structural constraints, normative expectations, and individual motivation as the joint influences of agency and structure in the service of life goals. Here, we examined undergraduates’ reasons for course choices for their most difficult and most important courses. We compared the reasons for non-major vs. major courses, for freshman vs. juniors, and across different disciplines. College students selected courses that fulfilled their major or breadth requirements, particularly in their freshman year. STEM courses were taken more for career development reasons than other disciplines, particularly humanities courses; social sciences courses were taken more for interest than STEM courses; and humanities courses were taken more for intellectual broadening than STEM courses.